Local adaptation is associated with zinc tolerance in Pseudomonas endophytes of the metal-hyperaccumulator plant Noccaea caerulescens - Fones, H; McCurrach, H; Mithani, A; Smith, J; Preston, G (Royal Society, The, 2016)
Metal-hyperaccumulating plants, which are hypothesized to use metals for defence against pests and pathogens, provide a unique context in which to study plant–pathogen coevolution. Previously, we demonstrated that the high concentrations of zinc found in leaves of the hyperaccumulator Noccaea caerulescens provide protection against bacterial pathogens, with a potential trade-off between metal-based and pathogen-induced defences. We speculated that an evolutionary arms race between zinc-based defences in N. caerulescens and zinc tolerance in pathogens might have driven the development of the hyperaccumulation phenotype. Here, we investigate the possibility of local adaptation by bacteria to the zinc-rich environment of N. caerulescens leaves and show that leaves sampled from the contaminated surroundings of a former mine site harboured endophytes with greater zinc tolerance than those within plants of an artificially created hyperaccumulating population. Experimental manipulation of zinc concentrations in plants of this artificial population influenced the zinc tolerance of recovered endophytes. In laboratory experiments, only endophytic bacteria isolated from plants of the natural population were able to grow to high population densities in any N. caerulescens plants. These findings suggest that long-term coexistence with zinc-hyperaccumulating plants leads to local adaptation by endophytic bacteria to the environment within their leaves.